Analyse und Beschreibung des mechanischen Werkstoffverhaltens von presshärtbaren Bor-Manganstählen - Stöhr, Thomas (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2012)
In the scope of this work was the improvement of the accuracy of FE models with regard to forming processes following the temperature-time profile of the hot stamping process. The focus of the investigations was on the determination and description of the forming behavior of boron manganese steels in dependency of process relevant influencing factors. Furthermore a methodology for the determination of true stress-strain curves at elevated temperatures in the layer compression test had been determined, enabling the rating of the stress state on the forming behavior of boron manganese steels. The distinctive improvement of the quality of the FE modeling of hot stamping processes utilizing the knowledge of this work had been shown in a comparison of the sheet thickness evolution of a numerically mapped and a experimentally formed componen